PENETAPAN KADAR NATRIUM PADA BUAH PISANG EMAS (Musa acuminate Colla.) SECARA SPEKTROFOTOMETRI SERAPAN ATOM - Vivi Purwandari; Ahmad Gazali Sofwan; Nelson Simanjuntak; Wantri Veronica (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
Bananas are the most consumed fruit by the people of Indonesia. This fruit has many health benefits including improving digestion, treating anemia, healthy bones, and improving nerve function. The nutritional content contained in bananas is carbohydrates, sugar, dietary fiber, fat, protein, vitamins, and minerals such as sodium, calcium, magnesium, phosphorus, potassium, and zinc. This study aims to determine the sodium content in golden bananas. The assay was carried out using an air-acetylene flame atomic absorption spectrophotometer. Quantitative analysis of sodium was carried out at a wavelength of 589.6 nm. The results of the study concluded that the sodium content of golden bananas was 1.8647 mg/100g. The results of the relative standard deviation test are 15% and have good precision because the results obtained for analytes with levels of parts per million are not more than 16% (Harmita, 2004).